User’s Learning Capability Aware E-Content Recommendation System for Enhanced Learning Experience - Vijayakumar, P.; Jagatheeshkumar, G. (International Journal of Intelligent Systems and Applications in Engineering, 2023)
E-learning is inevitable during these pandemic days and most of the learners find it comfortable to learn online. However, the main challenge is to locate the appropriate data in line with the learner’s requirement. Considering the necessity of this issue, this article presents an e-content recommendation system that considers the user’s learning capability. This work categorizes the documents into three categories such as basic, intermediate and advanced levels. Based on the users’ learning capability, corresponding documents are recommended and this idea enhances the overall learning experience. This work is based on three phases such as data pre-processing, feature extraction and classification. The collected documents are pre-processed for preparing the documents suitable for further processes. Features such as Parts-OF-Speech (POS) tagging, Term Frequency - Inverse Document Frequency (TF-IDF) and semantic similarity based on WordNet are extracted and the multiclass Support Vector Machine (SVM) is employed for distinguishing between the classes. The performance of the work is tested and the results prove the efficacy of the work with 98% accuracy rates, in contrast to the comparative techniques.